Surface Modiﬁcation of AISI H13 Tool Steel by Laser Cladding with NiTi Powder - B., Norhafzan; S. N., Aqida; E., Chikarakara; D., Brabazon (Springer, 2016)
This paper presents laser cladding of NiTi powder on AISI H13 tool steel surface for surface properties enhancement. The cladding process was conducted using Rofin DC-015 diffusion-cooled CO2 laser system with wavelength of 10.6 µm. NiTi powder was pre-placed on H13 tool steel surface. The laser beam was focused with a spot size of 90 µm on the sample surface. Laser parameters were set to 1515 and 1138 W peak power, 18 and 24 % duty cycle and 2300–3500 Hz laser pulse repetition frequency. Hardness properties of the modified layer were characterized by Wilson Hardness tester. Metallographic study and chemical composition were conducted using field emission scanning electron microscope and energy-dispersive X-ray spectrometer (EDXS) analysis. Results showed that hardness of NiTi clad layer increased three times that of the substrate material. The EDXS analysis detected NiTi phase presence in the modified layer up to 9.8 wt%. The metallographic study shows high metallurgical bonding between substrate and modified layer. These findings are significant to both increased hardness and erosion resistance of high-wear-resistant components and elongating their lifetime.